Procedural sedation in the ICU and emergency department. Issue 4 (August 2017) - Chawla, Nikhil; Boateng, Adjoa; Deshpande, Ranjit
Abstract : Purpose of review: Procedures are increasingly being performed in the acute care setting, outside of the operating rooms (OR). This article aims to review the current literature on out-of-OR procedural sedation with a focus on the ICU and emergency department, highlighting the following topics: multidisciplinary team approach, choice of pharmacologic agent, sedation scales, current safety guidelines, anticipating complications, appropriate monitoring and necessary resources. Recent findings: Subjective assessment of sedation using sedation scales is controversial. Addition of ketamine and dexmedetomidine to propofol for sedation improves patient and proceduralist satisfaction. The short-acting benzodiazepine remimazolam shows promise in initial phase 2 trials. Use of capnography for monitoring during sedation is being challenged by new literature from the emergency department setting. Hypoxia is the most common adverse event with procedural sedation, and the risk of pulmonary aspiration is low. Summary: Multimodal/synergistic sedation under a multidisciplinary team provides the best patient satisfaction. Collection and analysis of physiological data and outcomes of patients undergoing procedural sedation is necessary to maintain compliance with regulatory bodies. There is a paucity of comprehensive guidelines for conducting research in procedural sedation; therefore, it is being currently addressed by the Sedation Consortium.